Challenges in conducting online assessments in undergraduate medical and dental education: a scoping review - Gul Mehar Javaid Bukhari; Javeria Saleem; Syed Abdullah Javaid Bukhari; Muhammad Ishaq; Muhammad Salman Butt (BioMedica, 2022)
Online assessment in medical education is relatively new and there is a paucity of literature available on this topic. The objective of this scoping review was to conduct a systematic search of the published literature on the challenges of conducting online assessments in undergraduate medical and dental curricula. The literature was searched in the recommended electronic databases. The search terms used were “online assessments, e-assessments, computer-assisted assessments, online assessment challenges and opportunities, online assessments in medical education, reliability and validity of online assessments, and online assessments during COVID-19 pandemic” in PubMed Central, Google Scholar, Wiley Online Library, SpringerLink, and Ovid. After screening, 21 full-text articles were included in this scoping review. The data were charted independently and synthesized to present the findings. Most of the studies included in this review were published in the year 2020 and 2021(till September). Half of the studies (50%) reported that cheating and plagiarism are the most common challenges in online assessments, while a similar number of studies highlighted the issues faced by the teachers in making and conducting online assessments. Similarly, 22% of the studies emphasized the concerns raised by the students, while another 22% reported the technical and financial issues faced by the institutions in conducting online assessments. It was revealed that during COVID-19 the biggest challenge for the educational system was to switch to online assessments, as the educational system was not ready for it. Few studies (16%) reported that the issues of reliability and validity of online assessments are still to uncover. This scoping review may help to lay the foundation for more empirical future studies on the challenges of conducting online assessments in the undergraduate medical and dental curricula in Pakistan.